2020
DOI: 10.1186/s12981-020-00264-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV drug resistance in patients in China’s national HIV treatment programme who have been on first-line ART for at least 9 months

Abstract: Background: The aim of this study was to assess trends in drug resistance and associated clinical and programmatic factors at a national level during the rapid scale up of ART. Methods:Logistic regression was used to identify the factors associated with HIVDR. Variables associated with drug resistance in multivariable logistic regression were included in the Cochran-Armitage test for trend.Results: A total of 11,976 patients were enrolled in the study. The prevalence of HIVDR among patients who received ART fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…With the increase in the number of people receiving antiviral treatment, the risk of HIV drug resistance also increases, which may lead to the increase the transmissible drug resistance rate, it directly affects the effect of antiviral therapy. The drug resistance survey results of infected people receiving antiviral treatment showed that the national acquired drug resistance rate was 8.6% [54], and the drug resistance rate of infected people who fail to inhibit the virus exceeds 50% [55,56]. TDR was less frequent among individuals involved in clusters (1.95%) compared with those out of clusters (6.23%), which might be explained by several factors.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in the number of people receiving antiviral treatment, the risk of HIV drug resistance also increases, which may lead to the increase the transmissible drug resistance rate, it directly affects the effect of antiviral therapy. The drug resistance survey results of infected people receiving antiviral treatment showed that the national acquired drug resistance rate was 8.6% [54], and the drug resistance rate of infected people who fail to inhibit the virus exceeds 50% [55,56]. TDR was less frequent among individuals involved in clusters (1.95%) compared with those out of clusters (6.23%), which might be explained by several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical interventions are initiated upon detection of VL > 50 copies/mL in developed countries where frequent VL monitoring is performed, and the LLV is considered in the range of 50–200 copie/mL [ 33 ]. It should be noted that the definition of LLV remains 50–999 copies/mL in China, because most commercial resistance assays can only be performed on samples with VL above a minimum of 500–1000 copies/mL [ 19 , 27 , 34 , 35 ]. We conducted a systematic nationwide survey of HIVDR in patients with VL 50–999 copies/mL in China, and compared the results with those with VL ≥ 1000 copies/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, available studies from China performed integrase genotyping only on samples with VL ≥ 1000 copies/mL, few data are available on the emergence of such mutations in patients with LLV [ 22 25 ]. In recent years, in-house resistance assays can be performed on samples with VL below 1000 copies/mL, and the improvement of assays to quantify VL has led to progressively decrease the threshold of VF [ 7 , 21 , 26 , 27 ]. The high threshold for VF currently used in NFATP should be reconsidered.…”
Section: Introductionmentioning
confidence: 99%
“…It could be seen that the longer the antiviral time, the higher the proportion of drug resistance. With the increase in the number of people receiving antiviral treatment, the risk of HIV drug resistance also increases, which may lead to the increase the transmissible drug resistance rate, it directly affects the effect of antiviral therapy.The drug resistance survey results of infected people receiving antiviral treatment showed that the national acquired drug resistance rate was 8.6% [50], and the drug resistance rate of infected people who fail to inhibit the virus exceeds 50% [51,52].…”
Section: Discussionmentioning
confidence: 99%